CORRELATION BETWEEN HARRIS HIP SCORE (HHS) AND BODY MASS INDEX (BMI) IN PATIENTS WITH FEMORAL NECK FRACTURE AFTER HEMIARTHROPLASTY - Hutagalung, Muhammad Bayu Z; Rahman, Safrizal; Azharuddin, Azharuddin (JOINTS (Journal Orthopaedi and Traumatology Surabaya), 2018)
Femoral neck fracture is an intracapsular hip fracture. Hemiarthroplasty is one of the treatment options that replaces femoral aspect of hip joint with a prosthesis, while leaving the acetabulum intact. The treatment’s goal is to return the patient to premorbid capacity. Harris Hip Score (HHS) is an assessment for the outcome of hip surgery which contains: pain, functional capacity, deformity and range of motion (ROM). The purpose of study is to determine relation of BMI and Harris Hip Score (HHS) in patients with femoral neck fracture after hemiarthroplasty. This study is analytic-observational study with cross-sectional design conducted in June-September 2014 in Orthopedic’s Polyclinic of General Hospital dr. Zainoel Abidin Banda Aceh. Respondents in this study is 26. Comparative assessment of outcome was analysed by Kruskal-Wallis test with Mann-Whitney test as Post-hoc analysis and correlative assessment was analysed by Spearman test. Comparative assessment present significant relation of BMI (p = 0,006; r=0.458) with Harris Hip Score (HHS) in patients with femoral neck fracture after hemiarthroplasty.